2013
DOI: 10.1063/1.4795141
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model for the electrical nanocontact on germanium for scanning spreading resistance microscopy applications

Abstract: Quantitative carrier profiling represents a key element in the process development of future nanoelectronic devices. During the last decade, scanning spreading resistance microscopy (SSRM) has evolved as the method of choice for two-dimensional carrier mapping due to its unique spatial resolution and high sensitivity when applied to silicon (Si)-based devices. While the electrical nanocontact between a SSRM probe and Si is well documented, the insight is insufficient to understand or make predictions about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The presence of residual O during the early growth phases of B‐doped diamond thin films via chemical vapour deposition (CVD) can be detrimental regarding the electrical properties of the diamond film, which, in turn, will impact nanoscopic diamond tips and electrode application . This is due to the interaction of O with the B‐containing gas by converting the B‐precursors into energetically stable B–O species, which are not incorporated into the diamond film.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of residual O during the early growth phases of B‐doped diamond thin films via chemical vapour deposition (CVD) can be detrimental regarding the electrical properties of the diamond film, which, in turn, will impact nanoscopic diamond tips and electrode application . This is due to the interaction of O with the B‐containing gas by converting the B‐precursors into energetically stable B–O species, which are not incorporated into the diamond film.…”
Section: Introductionmentioning
confidence: 99%
“…The latter represents the local spreading resistance underneath the tip which is directly linked to the local conductivity of the diamond material . Although the use of a metallic tip for such measurements is an obvious choice and we have demonstrated TiN tips for the SSRM analysis on Ge samples , they suffer from rapid wear when scanning on diamond surfaces. For the experiments in this work only diamond‐based tips are hard enough for successfully probing boron‐doped diamond interfaces.…”
Section: Methodsmentioning
confidence: 99%
“…SSRM is based on atomic force microscopy (AFM) and is the leading method for quantitative 2D‐carrier profiling, featuring ∼1 nm spatial resolution, a response function covering a wide dynamic range of carrier concentration and the capability for site‐specific analysis . SSRM has been demonstrated as a unique concept for the electrical characterization of semiconductor devices with successful applications toward silicon‐based metal‐oxide semiconductor field‐effect transistors (MOSFETs) , FinFETs , nanowire‐based transistors , and Ge‐based p‐MOSFET devices .…”
Section: Introductionmentioning
confidence: 99%
“…25 In practice, a stable electrical contact between the tip and the sample is critical to achieving reliable resistance recording, which is usually implemented by applying a relatively large contact-force of the AFM tip on the sample. 26 In the case of silicon, a force larger than 15 lN is needed for the probe to penetrate the native oxide layer on top of the silicon surface. 25 Nevertheless, we found that a much lower force is enough for ZnO to obtain stable results of SSRM owing to its relative softness (Mohs hardness: 4.5 for ZnO versus 7 for silicon) and the absence of the insulating top layer.…”
mentioning
confidence: 99%
“…determined by the effective radius of the tip-sample contact, which can be significantly smaller than that of the tip, whereas the spatial resolution of SCM depends determinedly on the entire volume of the depletion region in response to the modulating voltage, which can far exceed the dimension of the tip. 24,26 A profile of SSRM resistance along the line across a NW in Fig. 4(b) is plotted in Fig.…”
mentioning
confidence: 99%